Peran Inovasi Produk, Orientasi Pasar, dan Pemasaran Digital terhadap Kinerja UMKM di Kota Bandung pada Era Ekonomi Digital - Sudirjo, Frans (Jurnal Ekonomi dan Kewirausahaan West Science, 2026)
This study examines the impact of product innovation, market orientation, and digital marketing on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Bandung City within the context of the digital economy. A quantitative approach was used, with data collected from 135 MSMEs via a structured survey. Multiple regression analysis revealed that all three independent variables—product innovation, market orientation, and digital marketing—positively and significantly affect MSME performance. Among these, digital marketing had the strongest impact on performance, followed by market orientation and product innovation. The results suggest that MSMEs can significantly enhance their business outcomes by adopting innovative product strategies, understanding customer needs, and utilizing digital marketing tools. These findings provide valuable insights for MSMEs seeking to improve their competitiveness and for policymakers aiming to support MSMEs in the digital economy.